2013
DOI: 10.2147/dddt.s46983
|View full text |Cite
|
Sign up to set email alerts
|

New structure–activity relationships of chalcone inhibitors of breast cancer resistance protein: polyspecificity toward inhibition and critical substitutions against cytotoxicity

Abstract: Adenosine triphosphate-binding cassette subfamily G member 2 (ABCG2) plays a major role in cancer cell multidrug resistance, which contributes to low efficacy of chemotherapy. Chalcones were recently found to be potent and specific inhibitors, but unfortunately display a significant cytotoxicity. A cellular screening against ABCG2-mediated mitoxantrone efflux was performed here by flow cytometry on 54 chalcone derivatives from three different series with a wide panel of substituents. The identified leads, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Psoralea corylifolia is the dried fruit of the legume Psoralea corylifolia L. Many studies have shown that it contains a variety of active components, such as monoterpenols, monoterpenol dimers, flavonoids, chalcone, coumarins, isoflavones, and fatty acids (Hollander, 1992). It displays anti-inflammatory, cardiovascular protective, and hypoglycemic properties, and good pharmacological activity (Corrêa et al, 2008;Xu et al, 2019;Pietro et al, 2013). Bavachalcone is a chalcone compound with a 1,3-diphenylpropenone skeleton (Figure 1) isolated from the traditional Chinese medicine Fructus Psoraleae.…”
Section: Introductionmentioning
confidence: 99%
“…Psoralea corylifolia is the dried fruit of the legume Psoralea corylifolia L. Many studies have shown that it contains a variety of active components, such as monoterpenols, monoterpenol dimers, flavonoids, chalcone, coumarins, isoflavones, and fatty acids (Hollander, 1992). It displays anti-inflammatory, cardiovascular protective, and hypoglycemic properties, and good pharmacological activity (Corrêa et al, 2008;Xu et al, 2019;Pietro et al, 2013). Bavachalcone is a chalcone compound with a 1,3-diphenylpropenone skeleton (Figure 1) isolated from the traditional Chinese medicine Fructus Psoraleae.…”
Section: Introductionmentioning
confidence: 99%
“…From all evaluated substituents, 2′-naphthyl and 3′, 4′ methylene-dioxy-phenyl were the most effective ( Figure 2 ). Also, the substitution at position 4 of ring B is critical; in this position an O -benzyl residue is the most effective substituent for the inhibition and cytotoxicity [ 38 ]. Many other studies have demonstrated that chalcones are promising selective BCRP inhibitors [ 4 , 39 , 40 , 41 ], such as Compounds 1 and 2 ( Figure 3 ), which have now become good candidates for preclinical experiments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%